Dielectric-magnetic synergistic loss type electromagnetic wave absorbing material and preparation method and application thereof

CN122742367APending Publication Date: 2026-09-11SOUTH CHINA UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610632838.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-05-09
Publication Date
2026-09-11

AI Technical Summary

Technical Problem

[0003]然而,传统的电磁波吸收材料大多存在明显的缺陷,难以完全满足日益增长的实际应用需求,例如:还原氧化石墨烯(rGO)虽然具有轻质、比表面积大、介电损耗强、微观结构可设计等特性,但由于其电磁波损耗机制存在局限性,电磁能量的衰减主要依赖导电损耗与有限的偶极极化过程,导致其对宽频带电磁波的吸收效率低下,吸波性能十分有限;铁氧体材料虽然具有化学稳定性良好、低频特性好、阻抗匹配好等特性,但同时也存在密度大、吸收频带窄、温度稳定性较差(高温下磁性易衰减)、对制备工艺比较敏感等问题

Benefits of technology

[0023]本发明的有益效果是:本发明的介电-磁协同损耗型电磁波吸收材料具有密度小、匹配厚度小、吸收频带宽、吸收强度大、组分和性能可以灵活调节等优点,其在雷达隐身和电磁防护领域具有十分广阔的应用前景,且其制备方法简单、工艺可控、生产成本较低,适合进行大规模工业化生产和应用。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122742367A_ABST
    Figure CN122742367A_ABST
Patent Text Reader

Abstract

This invention discloses a dielectric-magnetic synergistic loss type electromagnetic wave absorbing material, its preparation method, and its application. The dielectric-magnetic synergistic loss type electromagnetic wave absorbing material of this invention comprises rGO aerogel and Ni distributed in the rGO aerogel. x Co 1‑x Fe2O4 magnetic nanoparticles x The range of values ​​for is 0≤ x ≤1. The preparation method of the dielectric-magnetic synergistic loss type electromagnetic wave absorbing material of the present invention includes the following steps: mixing graphene oxide and Ni x Co 1‑x Fe2O4 magnetic nanoparticles are dispersed in water, then subjected to a hydrothermal reaction, followed by freeze-drying. The dielectric-magnetic synergistic loss-type electromagnetic wave absorbing material of this invention possesses advantages such as low density, small matching thickness, wide absorption bandwidth, high absorption intensity, and flexible adjustment of composition and properties, making it a promising candidate for applications in radar stealth and electromagnetic protection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electromagnetic shielding technology, specifically to a dielectric-magnetic synergistic loss type electromagnetic wave absorbing material, its preparation method, and its application. Background Technology

[0002] With the rapid development of electronic information technology, the number of electronic devices and communication base stations has surged, and electromagnetic interference and radiation problems have become increasingly serious. Electromagnetic radiation not only causes signal interference between electronic devices, thus affecting communication accuracy and information security, but may also threaten human health. Electromagnetic wave absorbing materials are functional materials that can convert the energy of incident electromagnetic waves into heat or other forms of energy, and they have been widely used in the field of electromagnetic shielding.

[0003] However, most traditional electromagnetic wave absorbing materials have significant drawbacks, making it difficult to fully meet the growing demands of practical applications. For example, although reduced graphene oxide (rGO) has characteristics such as being lightweight, having a large specific surface area, high dielectric loss, and a designable microstructure, its electromagnetic wave loss mechanism is limited. The attenuation of electromagnetic energy mainly depends on conductivity loss and a limited dipole polarization process, resulting in low absorption efficiency for broadband electromagnetic waves and very limited absorption performance. Ferrite materials, while possessing good chemical stability, good low-frequency characteristics, and good impedance matching, also suffer from problems such as high density, narrow absorption bandwidth, poor temperature stability (magnetic attenuation at high temperatures), and sensitivity to fabrication processes.

[0004] Therefore, it is of great significance to develop an electromagnetic wave absorbing material with the characteristics of being "thin, light, wide, and strong" and whose composition and properties can be flexibly adjusted. Summary of the Invention

[0005] The purpose of this invention is to provide a dielectric-magnetic synergistic loss electromagnetic wave absorbing material, its preparation method, and its application.

[0006] The technical solution adopted in this invention is: A dielectric-magnetic synergistic loss electromagnetic wave absorbing material, comprising rGO aerogel and Ni distributed in rGO aerogel. x Co 1-x Fe2O4 magnetic nanoparticles x The range of values ​​for is 0≤ x ≤1.

[0007] Preferably, the rGO aerogel, Ni x Co 1-x The mass ratio of Fe2O4 magnetic nanoparticles is 1:0.4 to 0.8.

[0008] Preferably, the Nix Co 1-x Fe2O4 magnetic nanoparticles are CoFe2O4 magnetic nanoparticles, Ni 0.3 Co 0.7 Fe2O4 magnetic nanoparticles, Ni 0.5 Co 0.5 Fe2O4 magnetic nanoparticles, Ni 0.7 Co 0.3 At least one of Fe2O4 magnetic nanoparticles and NiFe2O4 magnetic nanoparticles.

[0009] Preferably, the Ni x Co 1-x The Fe2O4 magnetic nanoparticles have a particle size of 100nm to 300nm.

[0010] Preferably, the density of the dielectric-magnetic synergistic loss-type electromagnetic wave absorbing material is 0.04 g / cm³. 3 ~0.10g / cm 3 .

[0011] A method for preparing a dielectric-magnetic synergistic loss-type electromagnetic wave absorbing material as described above includes the following steps: Graphene oxide and Ni x Co 1-x Fe2O4 magnetic nanoparticles are dispersed in water, then subjected to a hydrothermal reaction, and then freeze-dried to obtain a dielectric-magnetic synergistic loss electromagnetic wave absorbing material.

[0012] Preferably, the Ni x Co 1-x Fe2O4 magnetic nanoparticles are prepared by a method comprising the following steps: dispersing nickel salt and / or cobalt salt, iron salt, polyethylene glycol and sodium acetate (CH3COONa) in ethylene glycol, followed by a solvothermal reaction, and then separating, purifying and drying the product to obtain Ni x Co 1-x Fe2O4 magnetic nanoparticles.

[0013] Preferably, the nickel salt is at least one of nickel chloride, nickel nitrate, and nickel sulfate.

[0014] Preferably, the cobalt salt is at least one of cobalt chloride, cobalt nitrate, and cobalt sulfate.

[0015] Preferably, the iron salt is at least one of ferric chloride, ferric nitrate, and ferric sulfate.

[0016] Preferably, the ratio of polyethylene glycol, sodium acetate, and ethylene glycol is 1 mL to 3 mL: 6 g to 8 g: 80 mL.

[0017] Preferably, the number-average molecular weight of the polyethylene glycol is 400 g / mol to 1000 g / mol.

[0018] Preferably, the solvothermal reaction is carried out at a temperature of 180℃ to 220℃ for a reaction time of 6h to 12h.

[0019] Preferably, the hydrothermal reaction is carried out at a temperature of 140℃ to 180℃ for a reaction time of 10h to 15h.

[0020] Preferably, the freeze-drying time is 24h to 72h.

[0021] An electromagnetic shielding device comprising the aforementioned dielectric-magnetic co-loss type electromagnetic wave absorbing material.

[0022] Application of a dielectric-magnetic synergistic loss type electromagnetic wave absorbing material as described above in the fields of radar stealth or electromagnetic protection.

[0023] The beneficial effects of this invention are: the dielectric-magnetic synergistic loss electromagnetic wave absorbing material of this invention has the advantages of low density, small matching thickness, wide absorption bandwidth, high absorption intensity, and flexible adjustment of composition and performance. It has a very broad application prospect in the fields of radar stealth and electromagnetic protection. Moreover, its preparation method is simple, the process is controllable, and the production cost is low, making it suitable for large-scale industrial production and application.

[0024] Specifically: 1) The dielectric-magnetic synergistic loss-type electromagnetic wave absorbing material of the present invention can be controlled by adjusting Ni x Co 1-x The composition of cations in Fe2O4 magnetic nanoparticles effectively modulates the magnetic and dielectric properties of electromagnetic wave absorbing materials, thereby achieving a synergistic match between dielectric loss and magnetic loss. 2) The dielectric-magnetic synergistic loss-type electromagnetic wave absorbing material of the present invention achieves a balance between conductive network continuity, interfacial polarization intensity, and magnetic loss capability, and can be used in low Ni... x Co 1-x Under certain conditions of Fe2O4 magnetic nanoparticle filling, electromagnetic wave absorbing materials can possess both strong absorption and wide bandwidth characteristics (for example, the lowest reflection loss RL can be achieved with an ultra-low filling amount of only 6wt% CoFe2O4 magnetic nanoparticles). min =-66.53dB, maximum effective absorption bandwidth EAB max =8.02GHz), with overall absorption performance superior to most reported ferrite-rGO composite absorbing materials, and has a very broad application prospect in the fields of radar stealth and electromagnetic protection. 3) The dielectric-magnetic synergistic loss electromagnetic wave absorbing material of the present invention contains a three-dimensional porous rGO aerogel structure, which not only facilitates multiple reflections and scattering of electromagnetic waves and extends the transmission path of electromagnetic waves, but also provides rich heterogeneous interfaces and enhances interface polarization loss. In addition, the conductive network formed by rGO can also ensure that the electromagnetic wave absorbing material has effective conductive loss, and finally achieves a wave absorption effect enhanced by multiple mechanisms. 4) The dielectric-magnetic synergistic loss electromagnetic wave absorbing material of the present invention is prepared by a simple hydrothermal-self-assembly method. This method is controllable, easy to operate, and easy to carry out large-scale industrial production. Attached Figure Description

[0025] Figure 1 The image shows a physical representation of the hydrogel and dielectric-magnetic synergistic loss-type electromagnetic wave absorbing material from Example 1.

[0026] Figure 2 This is a SEM image of the dielectric-magnetic synergistic loss-type electromagnetic wave absorbing material of Example 1.

[0027] Figure 3 The graph shows the test results of dielectric constant and loss factor of the dielectric-magnetic synergistic loss-type electromagnetic wave absorbing material of Example 1 in the frequency range of 2GHz to 18GHz.

[0028] Figure 4 This is a 3D reflection loss diagram of the dielectric-magnetic synergistic loss type electromagnetic wave absorbing material of Example 1 in the frequency range of 2GHz to 18GHz.

[0029] Figure 5 The images show the 3D reflection loss diagrams of the electromagnetic wave absorbing materials in Comparative Examples 1 to 4 in the frequency range of 2 GHz to 18 GHz. Detailed Implementation

[0030] The present invention will be further explained and described below with reference to specific embodiments.

[0031] Example 1: A dielectric-magnetic synergistic loss-type electromagnetic wave absorbing material is prepared by the following method: 1) 2 mmol of CoCl2·6H2O, 4 mmol of FeCl3·6H2O, 2 mL of polyethylene glycol (number average molecular weight of 400 g / mol) and 7.2 g of CH3COONa were added to 80 mL of ethylene glycol and ultrasonically dispersed for 30 min. The mixture was then transferred to a 100 mL polytetrafluoroethylene-lined reactor and reacted at 200 °C for 8 h. The product was then magnetically separated (by adsorption with a magnet), washed three times alternately with deionized water and ethanol, and then freeze-dried for 48 h to obtain CoFe2O4 magnetic nanoparticles (particle size of 100 nm to 300 nm). 2) Add 75 mg of graphene oxide to 30 mL of deionized water and stir magnetically for 1 h. Then add 45 mg of CoFe2O4 magnetic nanoparticles, disperse ultrasonically for 30 min, and then transfer to a 50 mL polytetrafluoroethylene-lined reactor. React at 160 °C for 12 h to obtain a hydrogel. 3) The hydrogel was washed three times alternately with deionized water and ethanol, and then freeze-dried for 48 hours to obtain a dielectric-magnetic synergistic loss electromagnetic wave absorbing material (density 0.07 g / cm³). 3 ).

[0032] Performance testing: 1) A physical image of the hydrogel and the dielectric-magnetic synergistic loss-type electromagnetic wave absorbing material (aerogel) in this embodiment is shown below. Figure 1 As shown (a is a hydrogel, b is a dielectric-magnetic synergistic loss type electromagnetic wave absorbing material).

[0033] Depend on Figure 1 As can be seen from 'a' in this embodiment, the hydrogel exhibits significant magnetic response behavior under the action of an external magnetic field, indicating that it has good magnetic characteristics.

[0034] Depend on Figure 1 As can be seen from b in this embodiment, the dielectric-magnetic synergistic loss type electromagnetic wave absorbing material can be stably placed on dandelion, indicating that its density is very low and it has the characteristics of being lightweight.

[0035] 2) The scanning electron microscope (SEM) image of the dielectric-magnetic synergistic loss-type electromagnetic wave absorbing material in this embodiment is shown below. Figure 2 As shown.

[0036] Depend on Figure 2 It can be seen that the CoFe2O4 magnetic nanoparticles are uniformly distributed on the surface and between the rGO sheets, and no obvious large-area aggregation phenomenon was observed. This indicates that the composite system has good structural dispersion and interfacial bonding. This uniform distribution helps to form rich heterogeneous interfaces, which can provide more active sites for interfacial polarization, thereby improving the electromagnetic wave attenuation capability of the electromagnetic wave absorbing material.

[0037] 3) The dielectric constant of the dielectric-magnetic synergistic loss-type electromagnetic wave absorbing material in this embodiment was tested using the coaxial method. ε′ ) and loss factor ( ε″ The measurement frequency range was 2GHz to 18GHz, and the test results were as follows: Figure 3 As shown.

[0038] Depend on Figure 3 It can be seen that: throughout the entire frequency band, ε′ and ε″ All maintained high values, and ε″The presence of obvious dispersion characteristics as the frequency increases indicates that the dielectric-magnetic synergistic loss electromagnetic wave absorbing material of this embodiment has good dielectric loss capability.

[0039] 4) The reflection loss of the dielectric-magnetic synergistic loss electromagnetic wave absorbing material of this embodiment was tested using the coaxial method (electromagnetic performance evaluation: when the reflection loss value is less than -10dB, the electromagnetic wave absorbing material can absorb 90% of the electromagnetic waves; when the reflection coefficient is less than -20dB, the electromagnetic wave absorbing material can absorb 99% of the electromagnetic waves). The measurement frequency range was 2GHz to 18GHz, and the obtained 3D reflection loss diagram is shown below. Figure 4 As shown.

[0040] Depend on Figure 4 It can be seen that when the matching thickness is 3.35mm, the minimum reflection loss RL of the dielectric-magnetic synergistic loss electromagnetic wave absorbing material in this embodiment is... min =-66.53dB, and when the thickness is 3.29mm, the effective absorption bandwidth EAB of the dielectric-magnetic synergistic loss type electromagnetic wave absorbing material in this embodiment is... max =8.02GHz, indicating that it has excellent absorption performance with strong absorption and wide bandwidth absorption.

[0041] Example 2: A dielectric-magnetic synergistic loss-type electromagnetic wave absorbing material is prepared by the following method: 1) 0.6 mmol of NiCl2·6H2O, 1.4 mmol of CoCl2·6H2O, 4 mmol of FeCl3·6H2O, 2 mL of polyethylene glycol (number average molecular weight 400 g / mol), and 7.2 g of CH3COONa were added to 80 mL of ethylene glycol and ultrasonically dispersed for 30 min. The mixture was then transferred to a 100 mL polytetrafluoroethylene-lined reactor and reacted at 200 °C for 8 h. The product was magnetically separated, washed three times alternately with deionized water and ethanol, and then freeze-dried for 48 h to obtain NiCl2·6H2O. 0.3 Co 0.7 Fe2O4 magnetic nanoparticles (particle size 100nm~300nm). 2) Add 75 mg of graphene oxide to 30 mL of deionized water, stir magnetically for 1 hour, then add 45 mg of Ni. 0.3 Co 0.7 Fe2O4 magnetic nanoparticles were ultrasonically dispersed for 30 min, then transferred to a 50 mL polytetrafluoroethylene-lined reactor, and reacted at 160 °C for 12 h to obtain a hydrogel. 3) The hydrogel was washed three times alternately with deionized water and ethanol, and then freeze-dried for 48 hours to obtain a dielectric-magnetic synergistic loss electromagnetic wave absorbing material (density 0.07 g / cm³).3 ).

[0042] Through testing (using the same method as in Example 1), when the matching thickness is 4.14 mm, the minimum reflection loss RL of the dielectric-magnetic synergistic loss electromagnetic wave absorbing material in this example is [data missing]. min =-60.6dB, and when the thickness is 3.14mm, the effective absorption bandwidth EAB of the dielectric-magnetic synergistic loss type electromagnetic wave absorbing material in this embodiment is... max =7.34GHz, it has excellent absorption performance with strong absorption and wide bandwidth absorption.

[0043] Example 3: A dielectric-magnetic synergistic loss-type electromagnetic wave absorbing material is prepared by the following method: 1) 1 mmol of NiCl2·6H2O, 1 mmol of CoCl2·6H2O, 4 mmol of FeCl3·6H2O, 2 mL of polyethylene glycol (number average molecular weight 400 g / mol), and 7.2 g of CH3COONa were added to 80 mL of ethylene glycol and ultrasonically dispersed for 30 min. The mixture was then transferred to a 100 mL polytetrafluoroethylene-lined reactor and reacted at 200 °C for 8 h. The product was magnetically separated, washed three times alternately with deionized water and ethanol, and then freeze-dried for 48 h to obtain NiCl2·6H2O. 0.5 Co 0.5 Fe2O4 magnetic nanoparticles (particle size 100nm~300nm). 2) Add 75 mg of graphene oxide to 30 mL of deionized water, stir magnetically for 1 hour, then add 45 mg of Ni. 0.5 Co 0.5 Fe2O4 magnetic nanoparticles were ultrasonically dispersed for 30 min, then transferred to a 50 mL polytetrafluoroethylene-lined reactor, and reacted at 160 °C for 12 h to obtain a hydrogel. 3) The hydrogel was washed three times alternately with deionized water and ethanol, and then freeze-dried for 48 hours to obtain a dielectric-magnetic synergistic loss electromagnetic wave absorbing material (density 0.07 g / cm³). 3 ).

[0044] Through testing (using the same method as in Example 1), when the matching thickness is 4.27 mm, the minimum reflection loss RL of the dielectric-magnetic synergistic loss electromagnetic wave absorbing material in this example is [data missing]. min =-62.13dB, and when the thickness is 3.11mm, the effective absorption bandwidth EAB of the dielectric-magnetic synergistic loss type electromagnetic wave absorbing material in this embodiment is... max =7.26GHz, it has excellent absorption performance with strong absorption and wide bandwidth absorption.

[0045] Example 4: A dielectric-magnetic synergistic loss-type electromagnetic wave absorbing material is prepared by the following method: 1) 1.4 mmol of NiCl2·6H2O, 0.6 mmol of CoCl2·6H2O, 4 mmol of FeCl3·6H2O, 2 mL of polyethylene glycol (number average molecular weight 400 g / mol), and 7.2 g of CH3COONa were added to 80 mL of ethylene glycol and ultrasonically dispersed for 30 min. The mixture was then transferred to a 100 mL polytetrafluoroethylene-lined reactor and reacted at 200 °C for 8 h. The product was magnetically separated, washed three times alternately with deionized water and ethanol, and then freeze-dried for 48 h to obtain NiCl2·6H2O. 0.7 Co 0.3 Fe2O4 magnetic nanoparticles (particle size 100nm~300nm). 2) Add 75 mg of graphene oxide to 30 mL of deionized water, stir magnetically for 1 hour, then add 45 mg of Ni. 0.7 Co 0.3 Fe2O4 magnetic nanoparticles were ultrasonically dispersed for 30 min, then transferred to a 50 mL polytetrafluoroethylene-lined reactor, and reacted at 160 °C for 12 h to obtain a hydrogel. 3) The hydrogel was washed three times alternately with deionized water and ethanol, and then freeze-dried for 48 hours to obtain a dielectric-magnetic synergistic loss electromagnetic wave absorbing material (density 0.07 g / cm³). 3 ).

[0046] Through testing (using the same method as in Example 1), when the matching thickness is 3.26 mm, the minimum reflection loss RL of the dielectric-magnetic synergistic loss electromagnetic wave absorbing material in this example is [data missing]. min =-56.91dB, and when the thickness is 3.09mm, the effective absorption bandwidth EAB of the dielectric-magnetic synergistic loss type electromagnetic wave absorbing material in this embodiment is... max =7.54GHz, it has excellent absorption performance with strong absorption and wide bandwidth absorption.

[0047] Example 5: A dielectric-magnetic synergistic loss-type electromagnetic wave absorbing material is prepared by the following method: 1) 2 mmol of NiCl2·6H2O, 4 mmol of FeCl3·6H2O, 2 mL of polyethylene glycol (number average molecular weight of 400 g / mol) and 7.2 g of CH3COONa were added to 80 mL of ethylene glycol and ultrasonically dispersed for 30 min. The mixture was then transferred to a 100 mL polytetrafluoroethylene-lined reactor and reacted at 200 °C for 8 h. The product was magnetically separated and washed three times alternately with deionized water and ethanol. The product was then freeze-dried for 48 h to obtain NiFe2O4 magnetic nanoparticles (particle size of 100 nm to 300 nm). 2) Add 75 mg of graphene oxide to 30 mL of deionized water and stir magnetically for 1 h. Then add 45 mg of NiFe2O4 magnetic nanoparticles, disperse ultrasonically for 30 min, and then transfer to a 50 mL polytetrafluoroethylene-lined reactor. React at 160 °C for 12 h to obtain a hydrogel. 3) The hydrogel was washed three times alternately with deionized water and ethanol, and then freeze-dried for 48 hours to obtain a dielectric-magnetic synergistic loss electromagnetic wave absorbing material (density 0.07 g / cm³). 3 ).

[0048] Through testing (using the same method as in Example 1), when the matching thickness is 4.78 mm, the minimum reflection loss RL of the dielectric-magnetic synergistic loss electromagnetic wave absorbing material in this example is [data missing]. min =-69.71dB, and when the thickness is 3.16mm, the effective absorption bandwidth EAB of the dielectric-magnetic synergistic loss type electromagnetic wave absorbing material in this embodiment is... max =7.18GHz, it has excellent absorption performance with strong absorption and wide bandwidth absorption.

[0049] Comparative Example 1: An electromagnetic wave absorbing material, the preparation method of which is as follows: 1) Add 75 mg of graphene oxide to 30 mL of deionized water, stir magnetically for 1 h, then transfer to a 50 mL polytetrafluoroethylene-lined reactor, and react at 160 °C for 12 h to obtain a hydrogel. 2) The hydrogel was washed three times alternately with deionized water and ethanol, and then freeze-dried for 48 hours to obtain an electromagnetic wave absorbing material (density 0.04 g / cm³). 3 ).

[0050] Comparative Example 2: An electromagnetic wave absorbing material, the preparation method of which is as follows: 1) Add 75 mg of graphene oxide to 30 mL of deionized water, stir magnetically for 1 h, then add 5 mg of CoFe2O4 magnetic nanoparticles (same as in Example 1), disperse ultrasonically for 30 min, then transfer to a 50 mL polytetrafluoroethylene-lined reactor, and react at 160 °C for 12 h to obtain a hydrogel. 2) The hydrogel was washed three times alternately with deionized water and ethanol, and then freeze-dried for 48 hours to obtain an electromagnetic wave absorbing material (density 0.04 g / cm³). 3 ).

[0051] Comparative Example 3: An electromagnetic wave absorbing material, the preparation method of which is as follows: 1) Add 75 mg of graphene oxide to 30 mL of deionized water, stir magnetically for 1 h, then add 15 mg of CoFe2O4 magnetic nanoparticles (same as in Example 1), disperse ultrasonically for 30 min, then transfer to a 50 mL polytetrafluoroethylene-lined reactor, and react at 160 °C for 12 h to obtain a hydrogel. 2) The hydrogel was washed three times alternately with deionized water and ethanol, and then freeze-dried for 48 hours to obtain an electromagnetic wave absorbing material (density 0.05 g / cm³). 3 ).

[0052] Comparative Example 4: An electromagnetic wave absorbing material, the preparation method of which is as follows: 1) Add 75 mg of graphene oxide to 30 mL of deionized water and stir magnetically for 1 h. Then add 75 mg of CoFe2O4 magnetic nanoparticles (same as in Example 1), disperse ultrasonically for 30 min, and then transfer to a 50 mL polytetrafluoroethylene-lined reactor. React at 160 °C for 12 h to obtain a hydrogel. 2) The hydrogel was washed three times alternately with deionized water and ethanol, and then freeze-dried for 48 hours to obtain an electromagnetic wave absorbing material (density 0.08 g / cm³). 3 ).

[0053] Performance testing (testing method is the same as in Example 1): The 3D reflection loss diagrams of the electromagnetic wave absorbing materials in Comparative Examples 1-4 in the frequency range of 2GHz to 18GHz are shown below. Figure 5 (The numbers a to d in the figure correspond to scales 1 to 4 respectively).

[0054] Depend on Figure 5 From 'a' in the figure, we can see that the electromagnetic wave absorbing material in Comparative Example 1 is pure rGO aerogel, which only has dielectric loss and minimum reflection loss RL. min =-16.42dB, effective absorption bandwidth EAB max=4.27GHz, its wave absorption performance is poor, and the matching thickness is too thick.

[0055] Depend on Figure 5 As can be seen from b in Comparative Example 2, the amount of CoFe2O4 magnetic nanoparticles added to the electromagnetic wave absorbing material is small, resulting in a minimum reflection loss RL. min =-36.02dB, effective absorption bandwidth EAB max =7.58GHz, its wave absorption performance is poor and its contribution to magnetic loss is weak.

[0056] Depend on Figure 5 As can be seen from 'c', the electromagnetic wave absorbing material in Comparative Example 3 has a relatively small amount of CoFe2O4 magnetic nanoparticles added, resulting in a minimum reflection loss RL. min =-58.37dB, effective absorption bandwidth EAB max =7.82GHz, its wave absorption performance is improved compared with the electromagnetic wave absorbing material of Comparative Example 2, but it is still significantly lower than the dielectric-magnetic synergistic loss type electromagnetic wave absorbing material of Example 1.

[0057] Depend on Figure 5 As can be seen from d in Comparative Example 4, the electromagnetic wave absorbing material contains a large amount of CoFe2O4 magnetic nanoparticles. Excessive CoFe2O4 magnetic nanoparticles lead to a decrease in the continuity of the rGO conductive network, resulting in a lower minimum reflection loss RL. min =-56.80dB, effective absorption bandwidth EAB max =7.58GHz.

[0058] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention shall be considered equivalent substitutions and shall be included within the protection scope of the present invention.

Claims

1. A dielectric-magnetic synergistic loss electromagnetic wave absorbing material, characterized in that, The composition includes rGO aerogel and Ni distributed in the rGO aerogel. x Co 1-x Fe2O4 magnetic nanoparticles x The range of values ​​for is 0≤ x ≤1.

2. The dielectric-magnetic synergistic loss electromagnetic wave absorbing material according to claim 1, characterized in that: The rGO aerogel, Ni x Co 1-x The mass ratio of Fe2O4 magnetic nanoparticles is 1:0.4 to 0.

8.

3. The dielectric-magnetic synergistic loss electromagnetic wave absorbing material according to claim 1 or 2, characterized in that: The Ni x Co 1-x Fe2O4 magnetic nanoparticles are CoFe2O4 magnetic nanoparticles, Ni 0.3 Co 0.7 Fe2O4 magnetic nanoparticles, Ni 0.5 Co 0.5 Fe2O4 magnetic nanoparticles, Ni 0.7 Co 0.3 At least one of Fe2O4 magnetic nanoparticles and NiFe2O4 magnetic nanoparticles.

4. The dielectric-magnetic synergistic loss electromagnetic wave absorbing material according to claim 1 or 2, characterized in that: The Ni x Co 1-x The Fe2O4 magnetic nanoparticles have a particle size of 100nm to 300nm.

5. The dielectric-magnetic synergistic loss electromagnetic wave absorbing material according to claim 1 or 2, characterized in that: The density of the dielectric-magnetic synergistic loss-type electromagnetic wave absorbing material is 0.04 g / cm³. 3 ~0.10g / cm 3 .

6. A method for preparing a dielectric-magnetic synergistic loss type electromagnetic wave absorbing material as described in any one of claims 1 to 5, characterized in that, The steps include: mixing graphene oxide and Ni x Co 1-x Fe2O4 magnetic nanoparticles are dispersed in water, then subjected to a hydrothermal reaction, and then freeze-dried to obtain a dielectric-magnetic synergistic loss electromagnetic wave absorbing material.

7. The preparation method according to claim 6, characterized in that: The Ni x Co 1-x Fe2O4 magnetic nanoparticles are prepared by a method comprising the following steps: dispersing nickel salt and / or cobalt salt, iron salt, polyethylene glycol and sodium acetate in ethylene glycol, followed by a solvothermal reaction, and then separating, purifying and drying the product to obtain Ni x Co 1-x Fe2O4 magnetic nanoparticles.

8. The preparation method according to claim 6 or 7, characterized in that: The hydrothermal reaction is carried out at a temperature of 140℃ to 180℃ for a reaction time of 10h to 15h; and / or the freeze-drying time is 24h to 72h.

9. An electromagnetic shielding device, characterized in that, The material comprises the dielectric-magnetic synergistic loss type electromagnetic wave absorbing material as described in any one of claims 1 to 5.

10. The application of a dielectric-magnetic synergistic loss electromagnetic wave absorbing material as described in any one of claims 1 to 5 in the fields of radar stealth or electromagnetic protection.